2015
DOI: 10.1080/21632324.2015.1022084
|View full text |Cite
|
Sign up to set email alerts
|

Migration, life satisfaction, return and development: the case of a deprived post-Soviet country (Ukraine)

Abstract: This article explores the nexus between life (dis)satisfaction, migration aspirations and return and development within the context of a previously relatively developed but in the meantime deprived post-Soviet country, Ukraine. It is based on a mixed method quantitative and qualitative study conducted from 2010 to 2013. Three key findings have been emerging. First, life dissatisfaction significantly contributes to the emergence of migration aspirations and thus is an important driver of migration. This points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The literature on return migration and well‐being (Fuchs‐Schündeln & Schündeln, ; Lapshyna & Düvell, ; Mara & Landesmann, ) suggests that the intention to stay permanently, to move to another country, or to return to the country of origin is strongly influenced by migrants’ assessment of their life (life satisfaction). Nevertheless, these studies focus mainly on working‐age individuals, whereas little attention has so far been given to the impact of well‐being on the decision‐making process of ageing migrants.…”
Section: “Should I Stay or Should I Go?” Determinants Of Return Decismentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on return migration and well‐being (Fuchs‐Schündeln & Schündeln, ; Lapshyna & Düvell, ; Mara & Landesmann, ) suggests that the intention to stay permanently, to move to another country, or to return to the country of origin is strongly influenced by migrants’ assessment of their life (life satisfaction). Nevertheless, these studies focus mainly on working‐age individuals, whereas little attention has so far been given to the impact of well‐being on the decision‐making process of ageing migrants.…”
Section: “Should I Stay or Should I Go?” Determinants Of Return Decismentioning
confidence: 99%
“…Life satisfaction is related to how individuals appraise their life as a whole and it reflects the outcome of the migrants’ efforts to achieve a better life by the process of moving to another country, by staying abroad or by returning to the country of origin. Existing literature shows that migration decisions (both emigration and return) are not driven only by economic conditions, but also by the level of life (dis)satisfaction (Lapshyna & Düvell, ; Mara & Landesmann, ).…”
Section: “Should I Stay or Should I Go?” Determinants Of Return Decismentioning
confidence: 99%
“…Research shows that, on the one hand, job insecurity promotes the appreciation of one's workplace (Reiter, 2010) and on the other hand, the search for better conditions is negatively associated with staying in the same job for a longer period of time (Mussagulova et al, 2019). Besides, it is also observed that even people with higher levels of education, who have encountered difficulties, tend to emigrate to other countries not only from the post-Soviet space (Groutsis et al, 2020;Lapshyna & Düvell, 2015;White, 2016).…”
Section: Emotional State and Stay In The Jobmentioning
confidence: 99%
“…For instance, a study analysing migration trends in the United States (Castles, S., 2004) the author stresses the importance of political stability, respect for rights, development of civil society institutions in shaping migration trends. ese and some other factors of discomfort and life dissatisfaction grounded as a factors of emigration in researches considering the problem of migration in Central and Eastern Europe (Otrachshenko, V., Popova, O., 2013) and deprived post-Soviet countries (Lapshyna I., Düvell F., 2015).…”
Section: Literature Reviewmentioning
confidence: 99%